Antibacterial Effect of an Active Absorbent Pad on Fresh Beef Meat during the Shelf-Life: Preliminary Results - Marta Castrica; Dino Miraglia; Laura Menchetti; Raffaella Branciari; David Ranucci; Claudia M. Balzaretti (Applied Sciences, 2020)
Nowadays, active packaging plays a key role in the food sector, improving the safety and quality of food and, at the same time, extending its shelf life. The aim of the study was to evaluate the efficacy that an active absorbent pad has in limiting microbial growth during the shelf-life of fresh bovine meat. The experiment was carried out on 50 slices of eye of round (semitendinosus muscle) of an adult bovine, packaged in two different packs, one containing the conventional pad (C: Control group) and the other containing the active pad (PAD group). The analyses, performed at 0, 3 and 6 days of refrigeration storage (4 °C), concerned the pH, color, total volatile basic nitrogen (TVBN) and microbiological parameters. The packaging with the active pad had no noticeable effect on the pH, but with regard to the color coordinates, the meat at day 6 was lighter than the control group (p < 0.01). The innovative pad was able to delay the growth of all the microorganisms investigated, but only at day 3 (p < 0.05 to p < 0.001) compared to the control group. Furthermore, the TVBN values were lower than the control ones at both the third (p = 0.036) and sixth (p < 0.01) day of analysis. All samples were negative for coagulase positive staphylococci, L. monocytogenes, and Salmonella spp. In conclusion, following a preliminary examination, the packaging with the active pad was potentially effective in delaying microbial growth and it positively affected the color and TVBN of beef meat.